Analisis Komparatif Irasionalitas Ekonomi Pada Generasi Muda Berdasarkan Gender - Ava Putri Aurora; Ratna Fitri Astuti; Reza Reza; Sudarman Sudarman; Noor Ellyawati (Jayapangus Press, 2026)
Fulfillment of the needs of life demands that individuals should be able to choose the ideal economic decisions. The decision-making that individuals make to meet needs must be done rationally. When buying or using a product, individuals are supposed to assess and compare the quality of different brands, not just trust one option. The study aims to determine the comparison of economic irrationality behavior in the younger generation based on gender in Samarinda. The study used a quantitative approach with comparative analysis. The sample was 96 (48 men and 48 women) with respondents aged 16-30 years who were determined using the Lameshow formula with quota sampling technique. Data were collected through Likert scale research questionnaires and analyzed using descriptive statistics in the form of averages and percentages as well as comparative analysis with different tests of Independent Sample t-Test. The results showed that the Independent Sample t-Test obtained a significance value of 0.332 with a value of p>0.05, so that the hypothesis stating the absence of differences in irrationality between men and women is accepted. The young generation of men and women in Samarinda City have high economic irrationality behavior in purchasing decision making which is influenced by emotional, attachment to the price of goods, personal views, and the influence of social media and the social environment without rational consideration related to the needs and benefits of products.